Photon‐shot‐noise‐limited transient absorption soft X‐ray spectroscopy at the European XFEL. (20th February 2023) - Le Guyader, Loïc; Eschenlohr, Andrea; Beye, Martin; Schlotter, William; Döring, Florian; Carinan, Cammille; Hickin, David; Agarwal, Naman; Boeglin, Christine; Bovensiepen, Uwe; Buck, Jens; Carley, Robert; et al.
Abstract : A beam‐splitting off‐axis zone plate setup to measure transient X‐ray absorption spectroscopy is presented, as implemented at the Spectroscopy and Coherent Scattering instrument at the European X‐ray Free‐Electron Laser. Abstract : Femtosecond transient soft X‐ray absorption spectroscopy (XAS) is a very promising technique that can be employed at X‐ray free‐electron lasers (FELs) to investigate out‐of‐equilibrium dynamics for material and energy research. Here, a dedicated setup for soft X‐rays available at the Spectroscopy and Coherent Scattering (SCS) instrument at the European X‐ray Free‐Electron Laser (European XFEL) is presented. It consists of a beam‐splitting off‐axis zone plate (BOZ) used in transmission to create three copies of the incoming beam, which are used to measure the transmitted intensity through the excited and unexcited sample, as well as to monitor the incoming intensity. Since these three intensity signals are detected shot by shot and simultaneously, this setup allows normalized shot‐by‐shot analysis of the transmission. For photon detection, an imaging detector capable of recording up to 800 images at 4.5 MHz frame rate during the FEL burst is employed, and allows a photon‐shot‐noise‐limited sensitivity to be approached. The setup and its capabilities are reviewed as well as the online and offline analysis tools provided to users.